PASTURE MANAGEMENT AND GREENHOUSE GASES EMISSIONS - Cardoso, Abmael da Silva; Longhini, Vanessa Zirondi; Berça, Andressa Scholz [UNESP]; Ongaratto, Fernando [UNESP]; Siniscalchi, Debora [UNESP]; Reis, Ricardo Andrade [UNESP]; Ruggieri, Ana Cláudia [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2022)
Pastures are important environments worldwide because they offer many ecosystem services and sustain meat and milk production. However, pastures ecosystems are responsible for greenhouse gas (GHG) emission. The major GHGs include CO2, CH4, and N2O. The present review summarizes GHG emission from pasture ecosystems and discusses strategies to mitigate this problem. In pastures, emissions originate from animal excretion, fertilization, and organic matter decomposition. Emissions of specific gases can be measured based on certain factors that were recently updated by the United Nation’s Intergovernmental Panel on Climate Change in 2019. Urine is the main source of N2O emission. Forage structure is an important factor driving GHG transport. Forage fiber content and animal intake are the key drivers of enteric CH4 emission, and the introduction of forage legumes in pasture systems is one of the most promising strategy to mitigate GHG emission.
Keywords: Carbon Dioxide; Grazing Management; Methane; Nitrous Oxide